Severe Lipoatrophy in a Growth Hormone Deficient Toddler Girl Treated with a Non-Pegylated Long-Acting Growth Hormone - Atilla Büyükgebiz; And Demir (Children)
Background: Recombinant growth hormone (rhGH) has been used since 1985 to treat growth hormone (GH)-induced short stature, typically associated with transient adverse events. However, lipoatrophy, characterized by irreversible damage to subcutaneous fat, was first reported in 1999 and linked to antibody formation. In 2021, localized lipoatrophy was observed in 14.5% of patients receiving daily rhGH, with repeated injections at the same sites being a common contributing factor. Long-acting rhGH (LAGH) preparation offers the advantage of weekly injections, enhancing patient comfort and adherence to treatment. Methods: This case report discusses a 5.5-year-old girl born at 40 weeks of gestation with a birth weight of 2300 g, diagnosed with idiopathic short stature and borderline GH secretion, along with a history of mild intrauterine growth retardation. Results: After initiating treatment with somatrogon, a non-pegylated fusion protein formulation of LAGH at the standard dose of 0.66 mg/kg body weight weekly, administered by her family, she developed localized lipoatrophy at the injection site within eleven weeks. The injections were performed consistently in the same area of the right upper arm, where lipoatrophy emerged. Following the onset of this adverse effect, her treatment was adjusted to daily rhGH, with strict instructions to rotate injection sites. Despite these clear instructions, follow-up revealed that the parents continued to administer injections with the non-pegylated LAGH fusion protein formulation, this time in the left upper arm, leading to a recurrence of lipoatrophy within eight weeks. Conclusions: The recurrence underscores the importance of proper injection techniques, particularly site rotation, in preventing localized adverse effects. Given the limitations of this case, where the recommended adjustments were not followed by the parents, it is crucial to emphasize that the administration of the preparation should be discontinued immediately upon the appearance of side effects such as lipoatrophy. Individual reactions to drugs are always possible, and this highlights the need for clinician vigilance in monitoring and addressing adverse effects promptly during treatments with LAGH.